NY STATE ASSN FIRE CHIEFS LEGISLATIVE CO; NY STATE ASSN OF FIRE CHIEFS - SPAULDING RO (Tufts Archival Research Center, 2007)
Prototype of a letter from Anthony R. Granito to a legislator (name left blank, to be filled in later), asking for endorsement of the Boucher bill on fire safety which the Fire association has already endorsed.